Differential Coupling Double-Layer Coil for Eddy Current Testing With High Lift-Off - Chen, Kefan; Gao, Bin; Tian, Gui Yun; Yang, Yupei; Yang, Changrong; Ma, Qiuping (IEEE sensors journal, 2021)
The detection sensitivity and lift-off impaction of the eddy current sensing are the challenges in the field of electromagnetic nondestructive testing. Higher detection sensitivity, larger lift-off capability, and deeper defect detectability remain challenges. This paper presents a double-layer differential planar coil with the discussion of the most sensitive coupling gap. The upper layer contains two symmetrical excitation coils as it can generate symmetrical and opposite magnetic fields. The rectangular structure makes the induced current uniform and symmetrical. The lower layer constructs a differential receiving coil, which can reduce the interference caused by the lift-off impaction as well as the external magnetic field. Different types of surface defects of metallic materials were used for validation. Experimental results show that properly increasing the distance between the excitation and detection layers can effectively improve its sensitivity. Simulation and experimental results confirm that the performance of high sensitivity can be maintained under large lift-off affection.